(untitled) (Patan Prospective Journal, 2024)
Nepal, a predominantly agrarian nation, has experienced significant changes in its agricultural sector over the past three decades. Despite a rich agricultural base and a largely rural population, the country continues to face persistent food insecurity, increasing reliance on food grain imports, and stagnation of farm exports. This study examines these issues from 1990 to 2023, analyzing macroeconomic drivers using data from the Ministry of Agriculture and Livestock Development (MOALD), Nepal Rastra Bank (NRB), the World Bank (WB), and the Food and Agriculture Organization (FAO). The paper identifies structural challenges in Nepal’s agricultural sector by applying economic theories such as the Heckscher-Ohlin Model, Ricardian Comparative Advantage Theory, and New Economic Geography. It provides a data-driven analysis of trade imbalances, food security, and export performance. The findings highlight the need for targeted policy interventions to boost domestic agricultural productivity, diversify exports, and enhance regional cooperation. These strategies aim to mitigate food insecurity and improve agricultural trade outcomes.